EVOLUTIONARY MODEL OF FREE ECONOMIC ZONES IN THE REPUBLIC OF UZBEKISTAN - Sardor Bozarov; Ammar Younas (Scholar Express Journals, 2022)
Contemporary academia is proposing innovative legal frameworks, strategic economic policies, and financial models to enhance the productivity and promotion of the free economic zones. This article is an attempt to provide an analytical overview of the development of the free economic zones in Uzbekistan. A dissection of different stages of maturation of free economic zones have been highlighted. The first part of the article sheds a light on the genesis of the free economic zones, its legal progression and necessity to develop a strategic outline for the regulation of these zones in Uzbekistan. By utilizing a comparative methodological approach and doing a comprehensive analytical literature review of scholastic work, a nexus has been tried to build between different regional and international analogues projects. Finally, after relying on the available empirical evidence, this paper proposes more inclusive macro-objectives, investor-oriented legal regulatory mechanism, and multipreferential policy models for the development of Free Economic Zones in Uzbekistan
Keywords: Free Economic Zones; Legal Framework; Tax Preferences; Special Economic Zones